A "Culture" Shift: Broad Bacterial Detection, Identification, and Antimicrobial Susceptibility Testing Directly from Whole Blood. (4th January 2020) - Andini, Nadya; Hu, Anne; Zhou, Luming; Cogill, Steven; Wang, Tza-Huei; Wittwer, Carl T; Yang, Samuel
Abstract: BACKGROUND: The time required for bloodstream pathogen detection, identification (ID), and antimicrobial susceptibility testing (AST) does not satisfy the acute needs of disease management. Conventional methods take up to 3 days for ID and AST. Molecular diagnostics have reduced times for ID, but their promise to supplant culture is unmet because AST times remain slow. We developed a combined quantitative PCR (qPCR)-based ID+AST assay with sequential detection, ID, and AST of leading nosocomial bacterial pathogens. METHODS: ID+AST was performed on whole blood samples by ( a ) removing blood cells, ( b ) brief bacterial enrichment, ( c ) bacterial detection and ID, and ( d ) species-specific antimicrobial treatment. Broad-spectrum qPCR of the internal transcribed spacer between the 16S and 23S was amplified for detection. High-resolution melting identified the species with a curve classifier. AST was enabled by Ct differences between treated and untreated samples. RESULTS: A detection limit of 1 CFU/mL was achieved for Acinetobacter baumannii, Escherichia coli, Klebsiella pneumoniae, and Staphylococcus aureus. All species were accurately identified by unique melting curves. Antimicrobial minimum inhibitory concentrations were identified with Ct differences of ≥1 cycle. Using an RNA target allowed reduction of AST incubation time from 60 min to 5 min. Rapid-cycle amplification reduced qPCR times by 83% to 30 min. CONCLUSIONS: Combined, sequential ID+AST protocols allow rapid and reliable detection, ID, and AST for the diagnosis of bloodstream infections, enabling conversion of empiric to targeted therapy by the second dose of antimicrobials.